Effects of Collagen Hydrolysate-Based Protein Complexes on Physical Endurance, Glucose Metabolism, and Renal Function in Rats. - Kurkin, Denis V.; Bakulin, Dmitry A.; Osadchenko, Nazar A.; Murina, Natalia S.; Litvinova, Elena V. (Nutrients, 2026)
Background/Objectives: The increasing prevalence of nutrition-related diseases and the limited availability of convenient, metabolically safe, high-protein foods represent a pressing public health challenge. This study aimed to evaluate the effects of four composite animal-derived high-protein ingredients based on collagen enzymatic hydrolysates on physical endurance, feeding behaviour, carbohydrate metabolism, renal function, and behavioural parameters in rats. Methods: Four lyophilised collagen hydrolysate-based ingredients were developed using enzymatic biotransformation of bovine and porcine raw materials, combined with bovine whey protein concentrate, bovine meat trim hydrolysate, porcine blood plasma proteins, and an api-component (Samples 1–4; protein content 87–89%). Ninety male Wistar rats were randomised into one control group and four experimental groups (n = 20 per experimental group, n = 10 controls) and received test samples by intragastric gavage at 3000 mg/kg/day for 40 days. Physical endurance was assessed via a weighted forced swimming test (days 0, 30, and 40); behavioural status by open field, adhesive removal, and marble burying tests; and biochemical parameters (blood glucose, serum urea, creatinine, urinary protein, and GFR) at days 0 and 40. Results: All experimental groups demonstrated a significant reduction in standard chow consumption (19–24%, p < 0.01) without affecting body weight gain. Physical endurance improved significantly in all groups relative to baseline, with the most pronounced effect in the Sample 3 group (+39% at day 40, p < 0.05). Blood glucose levels were significantly reduced across all groups (9–16%, p < 0.05). No adverse behavioural effects were observed. Biochemical markers indicated an adaptive rather than pathological renal response, with elevated GFR in three of four experimental groups (p < 0.05) and reduced proteinuria in the Sample 1 and Sample 3 groups. Conclusions: Forty-day administration of collagen hydrolysate-based protein complexes improved physical endurance and glucose metabolism, reduced food intake without compromising body weight, and did not impair renal function or behavioural status in healthy adult rats. These findings support the potential of such ingredients as functional food components, pending confirmation of long-term safety in extended studies.